2003
DOI: 10.1016/s0736-0266(02)00085-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of intermittent hydrostatic pressure on osteoarthritic chondrocytes activated by bacterial endotoxin in vitro

Abstract: The role of continuous passive motion (CPM) in the management of septic arthritis and inflammatory arthritis remains of interest. CPM produces cyclic variations in intraarticular pressure that facilitates transport of fluid, nutrients, and solutes within and/ or across the joint and stimulates chondrocyte metabolism. However, the precise mechanisms mediating the responses of chondrocytes to joint motion remain unclear. This study tested the hypothesis that dynamic mechanical loading counteracts effects of bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Callus is similar to hyaline cartilage in morphology. A previous study demonstrated that joint movement can generate periodical pressure change in the joint, favorable to the in-joint exchange of nutrients and liquid via the synovial hole, which stimulates chondrocyte metabolism and promotes the synthesis of cartilage matrix protein and internal tissue reconstruction (10). …”
Section: Discussionmentioning
confidence: 99%
“…Callus is similar to hyaline cartilage in morphology. A previous study demonstrated that joint movement can generate periodical pressure change in the joint, favorable to the in-joint exchange of nutrients and liquid via the synovial hole, which stimulates chondrocyte metabolism and promotes the synthesis of cartilage matrix protein and internal tissue reconstruction (10). …”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, methicillin resistance in S. aureus and Group B Streptococcus infection have become an increasing problem and vancomycin, azithromycin remains the only effective antibiotic (Tissi et al 1995). Many recent reports were published on successful methods for treating septic arthritis such as gentamicin-impregnated polymethylmethacrylate beads (Brown and Bennett 1988), combination of antibiotics (cloxacillin) and free radical trap (α-phenyl-N-tert-butyl nitrone) which acts as anti-inflammatory and antioxidant (Sakiniene and Collins 2002), treatment with antibiotics and leptin (Hultgren and Tarkowski 2001), and continuous passive motion (CPM) (Lee et al 2003). We found that each clinical sign and radiographic finding detected in our patients such as mild fever, pain, joint swelling, degree of lameness were not specific to septic arthritis, even though their sensitivities were very high.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits from early instigation of exercise, in the form of continuous passive motion, have been demonstrated in experimental models (Salter et al, 1981) and reported in clinical cases in man (Parisien & Shaffer, 1990;Perry et al, 1992). Dynamic loading counteracts effects of inflammatory mediators, such as bacterial lipopolysaccharide, on chondrocyte metabolism, and it is suggested that this may have contributed to successful management of articular infection (Lee et al, 2003). Whenever possible, the authors recommend walking exercise to commence immediately after surgery and a graduated, controlled exercise program follows in line with tissue compromise.…”
Section: Postoperative Carementioning
confidence: 99%
“…Evidence that systemically administered therapeutic doses of nonsteroidal antiinflammatory drugs suppress deleterious effects of intrasynovial inflammatory mediators is lacking (May & Lees, 1996). These drugs may partially lessen release of factors involved in joint tissue breakdown (Lee et al, 2003), but administration of nonsteroidal antiinflammatory drugs effectively obviates use of clinical parameters, particularly lameness, in determining response to treatment (Gaughan, 1994;McIlwraith, 1983). Current opinion in assessing potential benefits of postoperative administration of nonsteroidal antiinflammatory drugs is therefore divided.…”
Section: Postoperative Carementioning
confidence: 99%